Kritik Sosial Dalam Naskah Drama Lena Tak Pulang Karya Muram Batubara Dan Implementasinya Sebagai Bahan Ajar Di SMK Negeri 9 Surakarta - Hanifiah, Umi; , Drs. Adyana Sunanda, M.Pd (2016)
ABSTRACT The purposes of this research are: (1) describing the structure of constuction, (2) describing the social criticism which exist in the drama script Lena Tak Pulang written by Muram Batubara, (3) expalining about the implementation of the result of the research of the drama script to be a teaching material for senior high school. The method of this research was descriptive-qualitative. The object of the research was social criticism. The data that was needed for this research was dialogues in Lena Tak Pulang drama. The sources were taken from drama script and other references that suitable with this research. Techniques of collecting data were divining manual technique and watch and write. Technique of validation was triangulation theory. Technique of data analysis was dialectic method. Based on the analysis, there were three result of the research, which were: (1) the structure that build the drama script of Lena Tak Pulang drama were the theme is about family, the actor and actress were Lena, Pak Lena, Bu Lena, guest 1, and guest 2; the plot was progressive, the place was Lena's porch, the time was in the evening and the duration was three days. (2) the social criticism of the drama script were social critique about moral and ethics; social critique about knowledge, social critique about logic and intellectuality, and social critique for hedonism; and (3) the result of the research was suitable with the literature learning in the XI grade semester 2. It was suitable to KD 3.1 memahami struktur dan kaidah teks film/ drama, baik secara lisan maupun tulisan, dan 4.1 memahami isi teks film dan drama untuk kurikulum 2013. Keywords: drama script Lena Tak Pulang, social criticism, and thaching materials in SMK N 9 Surakarta.